PERSEPSI MASYARAKAT TERHADAP FUNGSI-FUNGSI RUANG TERBUKA HIJAU TAMAN KACA MAYANG DAN TUNJUK AJAR INTEGRITAS DI PEKANBARU - Dawami, Daffa; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The sleeping land and public spaces available in Pekanbaru City are still extensive and some have been utilized and managed by the Riau Provincial Government and Pekanbaru City Government to become green garden spaces (RTH) such as Taman Puteri Kaca Mayang which is located in front of the Pekanbaru Walikota office and Taman Tunjuk Ajar Integritas in front of the residence of the Walikota of Pekanbaru. The location was originally managed by the private sector as a place for recreation and entertainment as well as an office area. Then, the Pekanbaru City Government transformed it into RTH by making a passageway between the two main roads that have been managed since 2017. This study seeks to examine the problem of how the people of Pekanbaru City perception of the green garden space functions and the factors that influence the formation of these perceptions. The theory used refers to the Social Perception Theory (Walgito, 2004) which includes recognition of certain objects, assessing and translating and giving attention based on individual knowledge and experience. This type of research uses a mixed method of quantitative and qualitative. Data were obtained from 80 visitor respondents, each of which was divided into 40 respondents in each RTH and grouped according to the classification of visitor respondents, namely the Head of Family, Housewives, Students, Youth/Students and Street Retaillers, which were taken incidentally. Then, supplemented with data from key informants from Pekanbaru City government officials and community leaders. The results showed that public perceptions of RTH Taman Kaca Mayang and Taman Tunjuk Ajar Integritas in Pekanbaru City were generally in a positive category, especially as a place for family recreation, children's playgrounds and a place for city residents to relax on holidays. The function as a place for family recreation is a necessity for visitors with a high educational background supported by dominant occupational professions as civil servants, military/police and private employees who have permanent jobs. Perceptions of other functions, such as economic, ecological and aesthetic functions have not been fully implemented. The contributing factors include, among other things, the limited funding factor which makes the facilities inadequate, the area is narrow, the lack of socialization, the green open space design follows the old spatial plan, the management is not professional and the human resources are low capacity. Research suggestions, minimize the inhibiting factors and strengthen the supporting factors to realize modern urban green garden space, in accordance with community needs and able to contribute to local revenue.Â Key words: Social Perception and Function of Green Garden Space (RTH).